Charge compensation, electrical and dielectric behavior of lanthanum doped CaCu3Ti4O12 - Dubey A.K.; Singh P.; Singh S.; Kumar D.; Parkash O. (My University, 2025)
Mechanism of charge compensation on lanthanum, (La3+) substitution on Ca site in calcium copper titanate (CaCu3Ti 4O12), and its effect on resulting electrical and dielectric properties has been studied in the present investigation. For this purpose samples were prepared according to two stoichiometries viz. La xCa(1-3x/2)Cu3Ti4O12 (x ≤ 0.09) and LaxCa(1-x)Cu3Ti 4O12 (x = 0.03) by solid state ceramic route. The former represents ionic compensation while the later is in accordance with electronic compensation. Nature of charge carriers is identified by measuring Seebeck coefficient which is found to be negative in the entire range of measurement. In order to understand the mechanism of conduction, ac conductivity is measured as a function of temperature and frequency. Space charge polarization is the dominant polarization mechanism phenomenon at low frequency and high temperature while orientation polarization dominates at low temperature and high frequency. Impedance analysis confirms the formation of internal barrier layers which is responsible for high dielectric constant in these samples. © 2010 Elsevier B.V. All rights reserved.